Perfil epidemiológico da malária em Cametá/Pará - ARAGÃO, Anderson Júnior dos Santos (2020)
Malaria is a protozoan characterized worldwide as one of the most serious public health problems, due to it remains one of the most important causes of morbidity and mortality in the tropical regions of the world. This study aimed to characterize the epidemiological profile of malaria in Cametá / PA, from january 2015 to december 2018. From the methodological point of view, the present study is a retrospective documentary and quantitative cross-sectional study, carried out in the municipality of Cametá / Pará, located in the Tocantins Health Region.The research was linked to the Dr. Ângelo Corrêa Municipal Health Center and the sample recruitment occurred through the analysis of data available in SIVEP-Malaria. In the period from 2015 to 2018, 22,323 tests were carried out in the municipality of Cametá to diagnose malaria, of which 39.19% (8.750 / 22.323) were positive for Plasmodium Sp. Of these, 87.71% (7.675 / 8.750) occurred in 2018 and 12.21% (1,069 / 8,750) in 2017. Out of the 8,750 registered cases, 7 794 (89.07%) were autochthonous. Regarding infectious Plasmodium species, 99.97% (8,748 / 8,750) of malaria cases were caudate by P. vivax, while 0.02% (2 / 8,750) resulted from P. falciparum infections. There were no reported cases of infections due to P. malariae, P. ovale and P. Knowlesi. With regard to sex, 60.66% (5.308 / 8.750) of the reported cases were men, while 39.32% (3,442 / 8750) were women. The age group most affected by malaria includes individuals with adulthood, followed by adolescents, children and the elderly. The percentage of children under 5 and the elderly afflicted by malaria was 17.48% (1,530 / 8,750). Of these 52.61% (805 / 1,530) were children while 47.38% (725 / 1,530) were elderly. Among the women affected by malaria in Cametá, 127 (3.68%) were pregnant. Of these, 23.62% (30/127) were in the first trimester of pregnancy, 34.64% (44/127) were in the second trimester and 37% (47/127) in the third trimester. The occurrence of annual malaria is perennial, being that the incidence of cases rises in less rainy months which comprise the so-called "Amazonian summer", with peak incidence in July, August and September. The lowest incidence of malaria is observed in the months of February, March and April, which present higher rainfall volumes. Regarding the annual parasitic incidence, in the year 2018 this was equivalent to 59.0 cases per 1000 inhabitants, classifying Cametá as high risk of transmission, being the localities of Inacha, Juaba, Marco da Legua, Jaçapetuba, Torres, Livramento, Maranhão , Arumau 1, Vila Conceição and Matias, which had the highest incidence in the municipality. These data highlight the worrisome epidemiological framework of malaria in the municipality of Cametá in accordance with its high epidemic potential resulting from the interaction of biological, environmental, socioeconomic and cultural factors, since the existence of the vector makes an area vulnerable to transmission when an infected man is present and has gametocytes.